Contribution of ellagic acid on the antioxidant potential of medicinal plant Epilobium hirsutum. (2nd January 2016) - Karakurt, Serdar; Semiz, Asli; Celik, Gurbet; Gencler-Ozkan, Ayse Mine; Sen, Alaattin; Adali, Orhan
Abstract: In the present study, the possible role of ellagic acid (EA) on antioxidant potential of Epilobium hirsutum ( EH ) in rat liver was investigated. Wistar rats were intraperitoneally treated with 37.5 mg/kg of EH and 10 mg/kg of EA for 9 days. Effects of EH and EA on antioxidant [glutathione peroxidase (GPx) and superoxide dismutases (SOD)] and Phase II [NADPH quinone oxidoreductase 1 (NQO1) and glutathione S-transferases (GSTs)] enzyme activities, as well as protein and mRNA expressions of those, were investigated. Polyphenolic content of EH was determined by LC-MS/MS analysis. EH and EA injection to rats resulted in a significant increase of NQO1 (3.6-fold and 4.7-fold), GPx (1.45-fold), and SOD (1.34-fold and 1.27-fold) enzyme activities, whereas total GST (46% and 57%) and its isoforms, and GST mu (57% and 72%), and GST theta (60% and 68%) activities were significantly decreased. Western-blot and qRT-PCR analysis showed that NQO1 and GPx protein and mRNA expressions were increased significantly ( P < 0.0001), whereas GST mu and GST theta were significantly decreased ( P < 0.0001).